5x+6(-2x-5)=-38-9x

Simple and best practice solution for 5x+6(-2x-5)=-38-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6(-2x-5)=-38-9x equation:


Simplifying
5x + 6(-2x + -5) = -38 + -9x

Reorder the terms:
5x + 6(-5 + -2x) = -38 + -9x
5x + (-5 * 6 + -2x * 6) = -38 + -9x
5x + (-30 + -12x) = -38 + -9x

Reorder the terms:
-30 + 5x + -12x = -38 + -9x

Combine like terms: 5x + -12x = -7x
-30 + -7x = -38 + -9x

Solving
-30 + -7x = -38 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-30 + -7x + 9x = -38 + -9x + 9x

Combine like terms: -7x + 9x = 2x
-30 + 2x = -38 + -9x + 9x

Combine like terms: -9x + 9x = 0
-30 + 2x = -38 + 0
-30 + 2x = -38

Add '30' to each side of the equation.
-30 + 30 + 2x = -38 + 30

Combine like terms: -30 + 30 = 0
0 + 2x = -38 + 30
2x = -38 + 30

Combine like terms: -38 + 30 = -8
2x = -8

Divide each side by '2'.
x = -4

Simplifying
x = -4

See similar equations:

| x^2+0.5x=0 | | -3(4.7y-5.8)+15.1y=9.5 | | -6/8/9/6 | | 4(2n-1)=(3n+5)+7 | | 1.6(z+7)-(5.9+0.6z)=-7+6 | | 7a+6-3a+9= | | 3m+2-3(m+1)=-(-7m+4) | | 15t+17=a-15 | | 6x-30=4 | | -341=15n | | 8-4x=13-5x | | 6+3n-2x-2= | | s+2(s+3)+(4s+-5)=148 | | 9x-4(2x+5)=-15 | | 2x+2(2x-1)=40 | | 5x-6-7x=-x-7 | | n=n*2-n | | 5b+2b-3-2b+7= | | 2(3x-4)+7=3x-2(x+1) | | 5(x+4)-4x=16 | | 3x(2a-2)-7= | | 7x+5b-4x-2b= | | s-2(s+3)+(4s-5)=148 | | 19c-9c= | | 9x-1(6x+3)=6 | | -3-7=6x+6-5x | | 8a+3x-5a+x= | | y/1.56=x | | n+0.1n+1.1=(n-1.5) | | s+5/2+10=38 | | 7+4=3r+6-2r | | 8x(2x+7)=-24 |

Equations solver categories